Clean Energy Innovation in Campus Environment with Small-Scale Wind Power Plants Integrated with IoT - artanto, dian; sutyasadi, petrus; Lukiyanto, Yohanes Baptista; Subanar, Gregorius Budi; Anurogo, Baskoro Latu; Halim, Enrico; Indratma, Samuel (Internet of Things and Artificial Intelligence Journal, 2025)
Universities as innovation centers have a strategic role in driving the clean energy transition through the implementation of small-scale wind power plants integrated with IoT. This article analyzes the potential of wind power technology in campus environments, which have an average low wind speed (3–5 m/s) through Savonius-type vertical axis turbines equipped with IoT modules for real-time monitoring of wind speed, wind direction, electrical energy production, and battery status. The results show that this technology is capable of producing 100–200 W of power with a wind energy conversion efficiency to electrical energy of up to 20-30%. The implementation of this technology not only increases energy independence but also becomes a renewable energy education platform for students. Multidisciplinary collaboration between the fields of electrical engineering, mechanical engineering, and informatics engineering is the key to system optimization, while green campus policies can accelerate the adoption of this technology nationally.